A simple optical fiber interferometer based breathing sensor. (2nd February 2017) - Li, Xixi; Liu, Dejun; Kumar, Rahul; Ng, Wai Pang; Fu, Yong-qing; Yuan, Jinhui; Yu, Chongxiu; Wu, Yufeng; Zhou, Guorui; Farrell, Gerald; Semenova, Yuliya; Wu, Qiang
Abstract: A breathing sensor has been experimentally demonstrated based on a singlemode–multimode–singlemode (SMS) fiber structure which is attached to a thin plastic film in an oxygen mask. By detecting power variations due to the macro bending applied to the SMS section by each inhalation and exhalation process, the breath state can be monitored. The proposed sensor is capable of distinguishing different types of breathing conditions including regular and irregular breath state. The sensor can be used in a strong electric/magnetic field and radioactive testing systems such as magnetic resonance imaging (MRI) systems and computed tomography (CT) examinations where electrical sensors are restricted.